Healthcare Resources Use in Patients with Human Immunodeficiency Virus (HIV). Real-World Evidence From Six Italian Local Health Units - Perrone, Valentina; Sangiorgi, Diego; Buda, Stefano; Andretta, Margherita; Borrè, Silvio; Cattaruzzi, Chiara; Gasperini, Gina; Lena, Fabio; Pisterna, Alessia; Degli Esposti, Luca (Farmeconomia. Health Economics and Therapeutic Pathways, 2018)
AIM: The aim of the study was to evaluate healthcare resource use and related costs for the management of people living with Human Immunodeficiency Virus (PLWHIV) with and without comorbidities, and to compare the burden of comorbidities in PLWHIV to the general population. METHODS: An observational retrospective analysis, based on administrative and laboratory databases from 6 Italian Local Health Units (LHUs) was performed. Individuals receiving either an HIV treatment [Antiretroviral therapy (ART) – ATC code: J05A)], or with an HIV positive laboratory test result between January 1st, 2014 and December 31st, 2014 were included. The date of first ART prescription or positive test of HIV was used as the Index Date (ID). Patients enrolled were followed-up for all time available from the ID (follow-up period) and their clinical characteristics were investigated from one year prior to the ID (characterization period). Comorbidities were measured by using the Charlson Comorbidity Index; findings were compared with those of a sample of the general population with the same age and sex distribution (OsMed 2015). Healthcare resource use and related cost was evaluated during the follow-up period. RESULTS: 1,214 patients were included, 837 were PLWHIV without any comorbidities and 377 were PLWHIV with at least one comorbidity. Mean prevalence of prescriptions for treatment of comorbidities was higher in the HIV-infected population than in the Italian general population. The annual healthcare cost of managing HIV patients with comorbidities, was significantly higher than that for patients without comorbidities (€ 10,615 vs. € 8,665, p < 0.001). CONCLUSIONS: Study results showed that 30% of PLWHIV had at least one comorbidity. The cost of managing PLWHIV who have comorbidities was significantly higher than that of managing PLWHIV without comorbidities. Our data confirm that care and treatment services should be adapted to address the specific needs of people living with both HIV and comorbidities.